Tissue damage during acute Trypanosoma cruzi infection is associated with reduced reparative regulatory T cell response and can be attenuated by early interleukin-33 administration - Boccardo, Santiago (2024)
Fil: Boccardo, Santiago. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Departamento de Bioquímica Clínica, Argentina.